The European Commission`s decisions against cartels influence on the companies` financial results - Jevdokimovs, Sergejs (Riga Graduate School of Law, 2019)
The main object of this thesis is the analysis of the European Commission`s decisions against cartels from the financial view. The analysis has been made about the influence on the financial results of the undertakings and their logic of the decision to be involved in the cartel. The proper analysis could not be made without analysis of the legal regulation and legal practice in this area, because the competition law is a symbiosis of these two disciplines. Thereby the legal description provides a detailed view of the possible risks for undertakings.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Competition law; Cartels